Postexercise syncope: Wingate syncope test and effective countermeasure - Lacewell, A. N.; Buck, T. M.; Romero, S. A.; Halliwill, J. R. (Experimental Physiology, 2014)
Altered systemic haemodynamics following exercise can compromise cerebral perfusion and result in syncope. As the Wingate anaerobic test often induces presyncope, we hypothesized that a modified Wingate test could form the basis of a novel model for the study of postexercise syncope and a test bed for potential countermeasures. Along these lines, breathing through an impedance threshold device has been shown to increase tolerance to hypovolaemia, and could prove beneficial in the setting of postexercise syncope. Therefore, we hypothesized that a modified Wingate test followed by head-up tilt would produce postexercise syncope, and that breathing through an impedance threshold device (countermeasure) would prevent postexercise syncope in healthy individuals. Nineteen recreationally active men and women underwent a 60 deg head-up tilt during recovery from the Wingate test while arterial pressure, heart rate, end-tidal CO2 and cerebral tissue oxygenation were measured on a control day and a countermeasure day. The duration of tolerable tilt was increased by a median time of 3 min 48 s with countermeasure in comparison to the control (P < 0.05), and completion of the tilt test increased from 42 to 67% with the countermeasure. During the tilt, mean arterial pressure was greater (108.0 ± 4.1 versus 100.4 ± 2.4 mmHg; P < 0.05) with the countermeasure in comparison to the control. These data suggest that the Wingate syncope test produces a high incidence of presyncope, which is sensitive to countermeasures such as inspiratory impedance.